15f-8f+13=-14

Simple and best practice solution for 15f-8f+13=-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15f-8f+13=-14 equation:


Simplifying
15f + -8f + 13 = -14

Reorder the terms:
13 + 15f + -8f = -14

Combine like terms: 15f + -8f = 7f
13 + 7f = -14

Solving
13 + 7f = -14

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 7f = -14 + -13

Combine like terms: 13 + -13 = 0
0 + 7f = -14 + -13
7f = -14 + -13

Combine like terms: -14 + -13 = -27
7f = -27

Divide each side by '7'.
f = -3.857142857

Simplifying
f = -3.857142857

See similar equations:

| -7-7n=-6n-2n | | -32f-12g=48 | | 2(9-7s)= | | -5*y=x^2 | | 2r-y-6=0 | | 4k(7k+5)= | | 12b^2-8=6b | | X+(-4)=-7 | | -10+2x=3x-1+8x | | 12b^2-8=ab | | x^2(x+7)=40x+100 | | (y^2)-23y+130=0 | | 7n+20=6 | | 200-6x=500-6x | | 4n+3+20=6 | | -16t^2+5t+92=0 | | Y+-3=8 | | 0=9x+25+5y | | 2.5x+1.2-4=3.5 | | 4-4b+3b=-3-5b+5b | | 9+x+x=29 | | -6x^2-5x+7=0 | | (6x+4)-(9x-4)= | | 12n-7=-2 | | 2(x-1)-5= | | 8y-12x=0 | | 11.70=2.10+0.80x | | 2x^2-150=650 | | -100=2(-8-6r) | | 19=x^2-17 | | (2x^2-7xy+6y^2)= | | 11(2-2x)+4= |

Equations solver categories